Assessment of gestational diabetes mellitus development in correlation with elevated first trimester serum uric acid levels - M., Anushaktha Reddy; S., Shridevi A.; Patil, Gayatri L. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: More than 10% of pregnancies in the world are affected with gestational diabetes mellitus (GDM), making it a prevalent pregnancy complication. The goal of this research was to examine whether or not higher serum uric acid levels in the first trimester of pregnancy are associated with an increased risk of developing GDM. Methods: The study was conducted on 56 first-trimester pregnant females at risk of GDM attending the outpatient clinic of the S. S. institute of medical sciences, Davanagere. All cases underwent estimation of uric acid levels <15 weeks, 24 to 28 weeks, and oral glucose challenge test (OGCT) at 24 to 28 weeks. Results: In our study, among 56 pregnant women, 17 (30.3%) developed GDM. Of these 12 women (70.6%) with GDM had higher uric acid levels and 5 women (29.4%) with GDM had normal uric acid levels. Uric acid levels were higher in women with a higher BMI. Conclusions: GDM development is significantly correlated with elevated serum uric acid levels in the first trimester. Early interventions by dietary and exercise regimes in these patients can reduce the maternal and neonatal complications.